A Silvicultura No Inpa - Higuchi, Niro (Acta Amazonica, 1981)
This report shows the evolution of Silviculture, in terms of research, during the 27 years of the existence of INPA (the National Institute for Research in the Amazon), from the first proposal in 1954 by the botanist Adolfo Ducke, to create a forest reserve, now the Ducke Forest Reserve, with also reference to the development of forestry in tropical Brazil. The silvicultural research tasks developed, and under development, by the Department of Tropical Silviculture, in the Ducke Forest Reserve (Km-26 along the Manaus-ltacoatiara Highway of 10,000 hectares), and in the Experimental Station of Tropical Silviculture (Km-45 along the Manaus-Caracaraí highway of 21.000 hectares), are briefly summarised. Regarding the tasks under development at this moment, the Project "Ecological Management and Exploitation of Moist Tropical Forest", In the Agriculture and Animal Husbandry District of SUFRAMA (Superintendency of the Free Zone of Manaus), starting at Km-14 along the access road ZF-2. has priority, with special emphasis on natural Regeneration. The report lists some conclusive results of the silvicultural works carried out at the field research stations of INPA.